Adaptive Design of Real-Time Control Systems subject to Sporadic Overruns - Pazzaglia, Paolo; Hamann, Arne; Ziegenbein, Dirk; Maggio, Martina (Proceedings - Design, Automation, and Test in Europe Conference and Exhibition, 2021)
Most off-the-shelf embedded control systems lack proper mechanisms to handle computational overload conditions. Therefore, delays may accumulate and produce overruns, potentially harming the stability and performance of the controlled system. In this paper, we explore a controller implementation in which overrun events are tolerated and tackled with a proper countermeasure, which can be easily plugged into existing controller implementations and in particular commercial off-the-shelf control systems. When an overrun occurs, the control period of the next job is reinitialized and its control parameters are adjusted to counteract the additional delay of the previous job. The main strength of this approach resides in a straightforward applicability and in a high flexibility in deployment. It does neither require a stochastic model of the timing evolution of the system, nor rely on prediction of future delays. We provide an exact tool to determine the system stability, which requires only the knowledge of the worst case response time. The final controlled system exhibits a good trade-off between simplicity and performance, both during nominal and overload conditions.